Increasing resilience in privileged access management - Kopra, Tomas (My University, 2023)
This Master of Science in Technology thesis, developed in collaboration with a target company, focuses on increasing resilience and disaster recovery planning for a privileged access management tool. The research was conducted using online sources and supplemented by available frameworks and best practices while working for the target organization. The thesis explorers several critical questions regarding privileged access rights: their nature, necessity to secure them, appropriate protection mechanisms, and ensuring the resilience of the protection mechanisms during potential disaster recovery scenarios. The research adopts design science research methodology, commencing with a literature review of identity and access management. The thesis progresses by identifying and assessing possible threat, incident and disaster scenarios for privileged access. The research then presents the most relevant scenarios and solution to enable resilience through high availability. The solutions is then evaluated. The research culminates in a conclusion that answers the set research questions.
Keywords: Disaster Recovery, Privileged Access Management, Identity and Access Management, High Availability.